2003
DOI: 10.1021/ol0348452
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Chemical Property of the First Fluorine-Containing Porphycene

Abstract: [structure: see text] A pyrrolic macrocycle, beta-tetrakis(trifluoromethyl)porphycene, is the first example of a fluorine-containing porphycene. Four electron-withdrawing CF(3) substituents provide a highly distorted structure and an attractive electron-deficient nature for the porphycene framework. From the electrochemical study, it is found that the LUMO energy level for the beta-trifluoromethylporphycene is 1.24 V more stabilized compared to that for etioporphyrin. Moreover, the deprotonation of the inner N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Two main strategies (Scheme 1) have been devised to obtain the precursor 5,5'-diacyl substituted 2,2'-bipyrroles (2): acylation (Y=alkyl group) [85,123] (or formylation, Y=H) [62,66,124,125] of an adequately 4,4'-disubstituted or 3,3',4,4'-tetrasubstituted 2,2'-bipyrrole (3 or 4, respectively), in one side, or transformation of 2,2'-bypyrroles bearing two latent formyl groups to aldehydes 2 (Y=H), two ester groups in the case of 5 [126] or two 4,4,6-trimethyl-1,3-dioxan-2-yl groups in the case of 6 (G=C 7 H 13 O 2 ), on the other side [127].…”
Section: The Ideal Pdt Sensitizermentioning
confidence: 99%
“…Two main strategies (Scheme 1) have been devised to obtain the precursor 5,5'-diacyl substituted 2,2'-bipyrroles (2): acylation (Y=alkyl group) [85,123] (or formylation, Y=H) [62,66,124,125] of an adequately 4,4'-disubstituted or 3,3',4,4'-tetrasubstituted 2,2'-bipyrrole (3 or 4, respectively), in one side, or transformation of 2,2'-bypyrroles bearing two latent formyl groups to aldehydes 2 (Y=H), two ester groups in the case of 5 [126] or two 4,4,6-trimethyl-1,3-dioxan-2-yl groups in the case of 6 (G=C 7 H 13 O 2 ), on the other side [127].…”
Section: The Ideal Pdt Sensitizermentioning
confidence: 99%
“…Sample preparations: Etioporphycene and b-tetrakis(trifluoromethyl) [18]/ [20]p porphycenes were synthesized according to the previously reported papers [17][18][19] and dissolved in toluene (Sigma-Aldrich, spectrophotometric grade).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [16] reported in 2007 that trifluoromethyl groups on pyrrole rings give rise to relatively air-stable [20]p porphyrin. After this work, Hayashi et al [17] also reported the successful synthesis and isolation of air-stable [20]p b-tetrakis(trifluoromethyl) porphycene ( [20]CF 3 Pc) through two-electron reduction and two protonation processes of [18]p b-tetrakis (trifluoromethyl)porphycene ([18]CF 3 Pc), which seems to be an analogue of etioporphycene ( [18]EtioPc) (Scheme 1). [18,19] Porphycene, the first porphyrin isomer, was synthesized by Vogel and co-workers in 1986, and a considerable number of research efforts have been conducted on novel synthesis, characterization, and applications of various porphycene derivatives over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In contrast, it is well-known that the introduction of electron-withdrawing groups at the peripheral position of the porphyrin framework stabilizes its LUMO energy level of the macrocycle. [5][6][7][8][9] Thus, it seems interesting to introduce electron-withdrawing groups at the peripheral positions of the porphycene to obtain an electron-deficient macrocycle, [10][11][12][13][14] although almost all porphycenes have only simple alkyl side chains as peripheral substituents such as methyl, ethyl, or butyl groups on the framework. [15][16][17] To further stabilize the LUMO energy level of porphycene, we have recently prepared the trifluoromethylated porphycene, 2,7,12,17-tetraethyl-3,6,13,16-tetrakis(trifluoromethyl)porphycene, Etio(CF 3 ) 4 PcH 2 .…”
mentioning
confidence: 99%
“…[15][16][17] To further stabilize the LUMO energy level of porphycene, we have recently prepared the trifluoromethylated porphycene, 2,7,12,17-tetraethyl-3,6,13,16-tetrakis(trifluoromethyl)porphycene, Etio(CF 3 ) 4 PcH 2 . 10 The four electron-withdrawing trifluoromethyl substituents provided an attractive electron-deficient nature with a dramatically decreased HOMO-LUMO gap in the porphycene framework. In addition, we initially determined that its iron -oxo complex, [{Fe III Etio(CF 3 ) 4 Pc} 2 -(-O)] (1), was readily converted into a monomeric iron(III) species, [Fe III Etio(CF 3 ) 4 Pc(py) 2 ] (2-Py 2 ), via the Fe-O bond cleavage and then reduced to a iron(II) complex in pyridine solution.…”
mentioning
confidence: 99%